2009
DOI: 10.1159/000245933
|View full text |Cite
|
Sign up to set email alerts
|

Classical Congenital Adrenal Hyperplasia due to 21-Hydroxylase Deficiency in Croatia between 1995 and 2006

Abstract: Aims: To evaluate the incidence, gender, symptoms and age at diagnosis among patients with classical congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency in Croatia. Methods: Data were collected retrospectively for all classical CAH patients born or electively aborted following prenatal diagnosis between 01.01.1995 and 31.12.2006 and were compared with the data of the previously conducted study evaluating CAH patients discovered between 1964 and 1984. Results: During a 12-year period, 34 class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…A significant linkage between the p.V282L mutation and the HLA‐A*33:01‐B*14:02‐DRB1*01:02 haplotype observed in our study is in concordance with previously reported results from other studies .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…A significant linkage between the p.V282L mutation and the HLA‐A*33:01‐B*14:02‐DRB1*01:02 haplotype observed in our study is in concordance with previously reported results from other studies .…”
Section: Discussionsupporting
confidence: 94%
“…Linkage disequilibrium has been demonstrated to exist between particular HLA-A, -B, and -DRB1 alleles or haplotypes and CYP21A2 mutations (9). The p.V282L mutation has been reported to be associated with the HLA-B14 antigen and -DR1 antigen among patients with NC form of the disease (10)(11)(12)(13), while some other studies reported on the association with a single HLA antigen, but a combination of those HLA specificities have not been reported before (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a relative paucity of males in a patient population may be taken as indirect evidence of unreported deaths from salt-wasting crises. Females do outnumber males in some (12,240,241) although not all (242) retrospective studies in which CAH was clinically diagnosed without neonatal screening. Moreover, there is a greater preponderance of severe genotypes in screened infants than in those ascertained prior to screening, again suggesting extra deaths of severely affected infants prior to screening (2,243).…”
Section: Benefitsmentioning
confidence: 98%
“…The majority of states in the United States (US) and more than 50 countries are currently performing NBS for CAH (5). Infant screening programs have markedly decreased the time to diagnosis, theoretically decreasing morbidity (6,7). Based on proven importance, a pilot NBS programme for CAH was initiated by the Turkish Directorate of Public Health (TDPH) on March 27, 2017 in four Turkish cities.…”
Section: Introductionmentioning
confidence: 99%